2004
DOI: 10.1186/1471-2458-4-55
|View full text |Cite
|
Sign up to set email alerts
|

The lack of public health research output from India

Abstract: BackgroundSystematic assessment of recent health research output from India, and its relation with the estimated disease burden, is not available. This information would help understand the areas in health research that need improvement in India to enhance the health of India's population.MethodsThe health research output from India during 2002, which was accessible in the public domain, was assessed by searching PubMed and other internet health literature databases, and was related to the disease burden sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
78
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(83 citation statements)
references
References 13 publications
4
78
1
Order By: Relevance
“…Listeriosis has been reported in sporadic, outbreak, and epidemic forms across many countries; however, data are lacking from developing countries such as India (Dandona et al, 2004;Reddy, 2006;Dandona et al, 2009). The absence of such data impedes epidemiological studies, which could otherwise be employed to control the spread of L. monocytogenes in developing countries.…”
Section: Introductionmentioning
confidence: 99%
“…Listeriosis has been reported in sporadic, outbreak, and epidemic forms across many countries; however, data are lacking from developing countries such as India (Dandona et al, 2004;Reddy, 2006;Dandona et al, 2009). The absence of such data impedes epidemiological studies, which could otherwise be employed to control the spread of L. monocytogenes in developing countries.…”
Section: Introductionmentioning
confidence: 99%
“…Dandona et al [7] conducted a study on the health research output. They concluded that both the magnitude and distribution of research output were not commensurate with the disease profile and burden.…”
Section: Introductionmentioning
confidence: 99%
“…[7] Dandona et al have out forward the concept of demand, supply, and environment for pushing research in India. [8] This may be the way forward. We cannot and should not regard research as the poor cousin of medicine.…”
Section: Letter To Editormentioning
confidence: 99%
“…Establishing and encouraging medical schools/ institutions to develop and train quality scientists should be regarded as a priority. [8] India today has a surprisingly few number of medical scientists. Medical and paramedical colleges should be encouraged to adopt a more hands-on investigative thinking culture in their teaching syllabus, as currently it is so theoretical that it rarely inspires enthusiasm in young professionals towards health research.…”
Section: Letter To Editormentioning
confidence: 99%